2014
DOI: 10.1093/geronb/gbu018
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use and Depression Among Retired Older Adults in the United States: A Longitudinal Analysis

Abstract: Our dynamic probit model indicates that for retired older adults in the United States, Internet use was found to reduce the probability of a depressed state by about 33%. Number of people in the household partially mediates this relationship, with the reduction in depression largest for people living alone. This provides some evidence that the mechanism linking Internet use to depression is the remediation of social isolation and loneliness. Encouraging older adults to use the Internet may help decrease isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
236
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(263 citation statements)
references
References 38 publications
23
236
0
4
Order By: Relevance
“…It provides a confirmatory test of previous research on the benefits of Internet use among older adults by showing that new technologies can also confer these benefits, particularly with respect to health outcomes. 2 It also provides a psychological mechanism through which technology can improve the lives of older adults. Previous research had been limited by considering technology use and quality of life in isolation of one another, rather than testing the psychological links between the two.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides a confirmatory test of previous research on the benefits of Internet use among older adults by showing that new technologies can also confer these benefits, particularly with respect to health outcomes. 2 It also provides a psychological mechanism through which technology can improve the lives of older adults. Previous research had been limited by considering technology use and quality of life in isolation of one another, rather than testing the psychological links between the two.…”
Section: Resultsmentioning
confidence: 99%
“…17 Indeed, there is a prospective link between Internet use and reduced depression that is mediated by decreases in loneliness and social isolation. 2 However, there are also a few studies showing no relationship between technology/Internet use and depression, quality of social relationships, and well-being. 18,19 There are also concerns that technological advances may even further isolate older adults from society, possibly leading to worse outcomes.…”
Section: The Benefits Of Social Technology Usementioning
confidence: 99%
“…This may be especially important in the context of loneliness, depression, and social isolation (Cotton, Anderson, & McCullough, 2013). For example, Cotten, Ford, Ford, and Hale (2014) analyzed four waves of the Health and Retirement survey and found that Internet Use contributed positively to the mental well-being of retired adults in the US, especially those living alone. They argue that Internet use allows retirees the opportunity to maintain relationships and exchange social support.…”
Section: Discussionmentioning
confidence: 99%
“…Although social contact via the internet may be less affected by functional limitations, it remains uncertain whether such contact actually improves social well-being among older adults. Observational studies suggest that adults who use the internet are less likely to be depressed compared to adults who did not report internet use ( Shelia R. Cotten, Ford, Ford, & Hale, 2014). However, experimental studies on the protective effect of internet use on social contact and loneliness have been mixed to negative (Slegers, van Boxtel, & Jolles, 2008; White et al, 2002), perhaps due to the limited social network of older adults enrolled in the trials.…”
Section: Discussionmentioning
confidence: 99%